2017
DOI: 10.1371/journal.pntd.0005724
|View full text |Cite
|
Sign up to set email alerts
|

Transmission risk of two chikungunya lineages by invasive mosquito vectors from Florida and the Dominican Republic

Abstract: Between 2014 and 2016 more than 3,800 imported human cases of chikungunya fever in Florida highlight the high risk for local transmission. To examine the potential for sustained local transmission of chikungunya virus (CHIKV) in Florida we tested whether local populations of Aedes aegypti and Aedes albopictus show differences in susceptibility to infection and transmission to two emergent lineages of CHIKV, Indian Ocean (IOC) and Asian genotypes (AC) in laboratory experiments. All examined populations of Ae. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 59 publications
2
78
0
Order By: Relevance
“…aegypti [126,127,144,161–164,164–166], Ae. albopictus [127,144,162,164–167], Aedes terrens [168], and Haemagogus leucocelaenus [168] are all experimentally competent to transmit chikungunya virus. Chikungunya virus transmission in Ae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti [126,127,144,161–164,164–166], Ae. albopictus [127,144,162,164–167], Aedes terrens [168], and Haemagogus leucocelaenus [168] are all experimentally competent to transmit chikungunya virus. Chikungunya virus transmission in Ae.…”
Section: Resultsmentioning
confidence: 99%
“…aegypti with Zika, chikungunya and dengue viruses minimally affected vector competence, and that vectors were able to transmit each viral pair, as well as three viruses simultaneously. Alto et al [167] found Ae. aegypti and Ae.…”
Section: Resultsmentioning
confidence: 99%
“…aegypti with Zika, chikungunya and dengue viruses minimally affected vector competence, and that vectors were able to transmit each viral pair, as well as three viruses simultaneously. Alto et al [69] found Ae. aegypti and Ae.…”
Section: Virus Transmission Dynamicsmentioning
confidence: 98%
“…aegypti [46,[63][64][65][66][67][68], Ae. albopictus [46,64,[66][67][68][69], Aedes terrens [70], and Haemagogus leucocelaenus [70] are all experimentally competent to transmit chikungunya virus. Chikungunya virus transmission in Ae.…”
Section: Vector Species Compositionmentioning
confidence: 99%
“…luteocephalus, Ae. neoafricanus have been revealed as vectors in sylvatic cycle, though, mainly in Africa [7,8]. Moreover, Culex species as a transmission vector for CHIKV in humans and birds has been mainly reported in Italy, France, Zimbabwe, Philippines and South Africa [9].…”
Section: Introductionmentioning
confidence: 99%